Assessment of genetic diversity using morphological traits in pigeonpea [Cajanus cajan (L.) Millsp.] - Vankat R. Pandey (Electronic Journal of Plant Breeding, 2019)
The nature and magnitude of genetic diversity was assessed among 120 genotypes of pigeonpea along with three checks in augmented design during Kharif, 2011-12. The Non-hierarchical Euclidean cluster analysis grouped all the genotypes into twelve distinct non-overlapping clusters indicated existence of high degree of genetic diversity in the materials. The crossings between the members of diverse clusters separated by high inter-cluster distances are likely to throw desirable segregants. In this context, very high inter cluster distances were recorded between cluster VI and XII, cluster V and XII, cluster II and IX, cluster VI and XI, cluster II and VI and cluster V and IX. Considering the mean performance for different characters of genotypes belonging to diverse clusters, the promising genotypes for exploitation as parents in breeding programme were NDAGC 2011-4, NDAGC 2011-42 and NDAGC 2011-2 of cluster II; NDAGC 2011-18, NDAGC 2011-58, NDAGC 2011-34 and NDAGC 2011-27 of cluster V; NDAGC 2011-16, NDAGC 2011-41, NDAGC 2011-88, NDAGC 2011-104 and NDAGC 2011-103 of cluster VI; IC 525504 and Pusa 33 of cluster IX and IC 525456, IC 525408 and IC 525463 of cluster XII. It may be concluded that crosses between diverse genotypes belonging to clusters separated by high inter-cluster distances with desired means are likely to produce transgressive segregants may be advocated for developing high yielding pigeonpea varieties.